Implementation of Community Based Tourism in the Development of Kampung Lawas Maspati in Surabaya City - Chorida Maulidil Zahrotul Ulya; Dewi Casmiwati (UNIVERSITAS SERAMBI MEKKAH, 2024)
Kampung Lawas Maspati, which is located on Jl. Maspati, Bubutan District, Surabaya City has many achievements. Kampung Lawas Maspati also has a historical icon and local wisdom that is still maintained. The people of Kampung Lawas Maspati implement a community based tourism destination. The purpose of this study is to describe and analyze the application of community-based tourism of Kampung Lawas Maspati in Surabaya City. The research method used is descriptive with a qualitative approach. The theory uses the Community Based Tourism (CBT) theory according to Suansri. The results of this study show that the application of community-based tourism in the development of Kampung Lawas Maspati is still not successful, because there is still no regeneration in managing Kampung Lawas Maspati into a tourist village. Kampung Lawas Maspati has been good and has become an independent and more developed Village. Beside that, the community benefits from the development of Kampung Lawas Maspati, Surabaya.